Peel bond strength of soft lining materials with antifungal to a denture base acrylic resin - Sanchez-Aliaga, Adelaida; Guimaraes Pellissari, Claudia Viviane [UNESP]; Arrais, Cesar Augusto Galva; Michel, Milton Domingos; Neppelenbroek, Karin Hermana; Urban, Vanessa Migliorini (Japanese Soc Dental Materials Devices, 2016)
The effect of the addition of nystatin, miconazole, ketoconazole, chlorhexidine, and itraconazole into the soft lining materials Softone and Trusoft on their peel bond strength to a denture base acrylic resin was evaluated. Specimens of soft lining materials (n=7) were made without (control) or with the incorporation of antifungals at their minimum inhibitory concentrations to the biofilm of C. albicans and bonded to the acrylic resin. Peel testing was performed after immersion in distilled water at 37 degrees C for 24 h, 7 and 14 days. Data (MPa) were analyzed by 3-way ANOVA/Tukey-Kramer test (alpha=0.05) and the failure modes were classified. The addition of nystatin and ketoconazole did not affect the peel bond strength for up to 14 days. Most failures were predominantly cohesive within soft lining materials. With the exception of itraconazole, incorporating the antifungals into the soft lining materials did not result in values below those recommended for peel bond strength after 7 and 14 days of analysis.
Keywords: Denture stomatitis; Soft lining materials; Candida albicans; Anti-infective agents; Peel strength